Association between breast cancer and tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) gene 1595C/T SNP in a Pakistani population - Rehman, Saima F.; Mansoor, Qaisar; Farooqi, Ammad A.; Nazir, Nusrat; Kausar, Rukhsana; Jabeen, Nyla; Ismail, Muhammad (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the Study : TRAIL-mediated signalling has emerged as an extensively studied biological mechanism reported to differentially induce apoptosis in cancer cells. However, overwhelmingly increasing experimentally verified data is shedding light on resistance against TRAIL-induced apoptosis in cancer cells. Moreover, genetic and epigenetic mutations also exert effects on the functionality of TRAIL and its receptors. In this study we investigated the association between breast cancer and polymorphisms in tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in a Pakistani Population. Material and methods: Genotyping for TRAIL gene 1595 C/T polymorphism was done for 363 breast cancer patients and 193 age- and sex-matched healthy controls. DNA was extracted using standard organic methods. PCR-RFLP analysis was done for C/T polymorphism at position 1595 in exon 5 of the TRAIL gene using site-specific primers and restriction enzyme. The results were statistically evaluated by SPSS14. Results : In this study, CC homozygotes were 46.3% in patients and 49.7% in controls, p = 0.729 with OR value 0.8705 (95% CI: 0.6137–1.2348). CT was statistically insignificant, p = 0.837 with OR value 0.9242 (95% CI: 0.6494–1.3154). However, the minor allele or risk allele genotype TT had a higher percentage among breast cancer patients (12.1%) than in the control group (6.7%). Since there was a statistically insignificant difference (p = 0.212, OR value 1.9098 with 95% CI 1.0019 to 3.6406) of TT genotype between the two groups, the contrastingly higher percentage of TT genotype in breast cancer patients seems to be a risk factor for the disease. Moreover, the frequency of minor allele T was also found to be higher in the patients (0.329) than in the controls (0.285). Conclusions : The TRAIL gene 1595 C/T SNP has a contradictory role in cancer development in different populations. In our population group although the percentage of homozygous risk allele TT was higher in patients it was statistically non-significant. The raised T allele and TT genotype in patients may suggest its association with breast cancer in the Pakistani population.